2005
DOI: 10.1093/ndt/gfh750
|View full text |Cite
|
Sign up to set email alerts
|

Diphenyleneiodium (DPI) reduces oxalate ion- and calcium oxalate monohydrate and brushite crystal-induced upregulation of MCP-1 in NRK 52E cells

Abstract: Exposure to Ox ions, and COM and Br crystals stimulates a ROS-mediated increase in MCP-1 mRNA expression and protein production. Reduction in ROS production, lipid peroxidation, low-density lipoprotein release, and inducible MCP-1 gene and protein in the presence of DPI indicates an involvement of NADPH oxidase in the production of ROS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 28 publications
4
58
1
Order By: Relevance
“…The concentration of oxalate in the urine changes as it moves through the nephron and is 0.22 mM in normal excreted urine, 0.44 mM in conditions of mild hyperoxaluria, and 1.5 mM in primary hyperoxaluria. Various studies have used 0.1-4 mM oxalate [30][31][32] for exposure of renal epithelial cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of oxalate in the urine changes as it moves through the nephron and is 0.22 mM in normal excreted urine, 0.44 mM in conditions of mild hyperoxaluria, and 1.5 mM in primary hyperoxaluria. Various studies have used 0.1-4 mM oxalate [30][31][32] for exposure of renal epithelial cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that Ox and/or CaOx crystals may induce oxidative stress in kidneys and lead to an increased production of free radical, resulting in cell damage or cell death in renal tissue; however, this hypothesis should be tested by further studies. Then, crystal retention can be promoted due to increased exposure of crystal attachment sites as a result of tubular cell detachment or membrane structure alteration after oxalate and/or crystal injury, as proposed previously [26][27][28].…”
Section: Discussionmentioning
confidence: 87%
“…The attraction of inflammatory cells is thought to be caused by chemotactic proteins. The over-production of MCP-1 chemokine and IL-6 cytokine by crystal-exposed renal tubular cells was reported [10][11][12][13][14]16]. We hypothesized that MCP-1 and IL-6 were up-regulated in the kidney of patients with stones, and their increased contributed to renal dysfunction.…”
Section: Discussionmentioning
confidence: 91%
“…Evidence from cell-culture models confirmed that MCP-1 was up-regulated in renal tubular cell lines challenged with oxalate ions/ crystals, and its expression was attenuated by antioxidants [10][11][12][13][14]. Furthermore, there was crystal-induced up-regulation of MCP-1 and osteopontin in renal fibroblast cells [15].…”
Section: Introductionmentioning
confidence: 90%